Academic activism: learning and self-transformation through collective action taking - Zourou, Katerina; Potolia, Anthippi; Oikonomou, Stefania (Frontiers in Education, 2024)
Activism, as a manifestation of citizen engagement for social purposes, can be practised by individuals and communities alike, such as communities of professionals and, in this case, professionals in academia. Academic activism is a novel form of socio-political engagement in scholarly communities. Recently, communities engaged in academic activism have multiplied, mostly due to the climate emergency and increased awareness on human-induced climate change. This paper focuses on the learning elements and self-transformative potential of becoming an academic activist. This is done by analysing three key areas: a) the perceptions of self, b) the learning component, and c) the educational component, namely teaching the very activities that activists carry out at their universities. To serve these objectives, we conducted eight semi-directive interviews during the summer of 2022 in which participants drew upon their personal experience and life trajectories in their journey to becoming academic activists. Using a Discourse Analytical framework, we scrutinised the semantic fields summoned and the discursive spaces mobilised by the interviewees. The findings of this study highlight the participants' determination for activism, depicting it as a conscious act, a duty. Moreover, three types of learning have been depicted, demonstrating the wealth of learning trajectories experienced. The potential impact of academic activism on teaching practices (societal role of education) has also been depicted.